Heat transfer enhancement in drag-reducing channel flow - Yeo, Keng Hoo (2008)
Since the discovery of the Toms effect (Toms, 1948), polymers as drag-reducing additives have been widely used to reduce the undesired drag that occurs over long-distance transportation of liquids. However, less attention has been focused on this area of research, especially in the case of re-circulating flow systems. This is mainly due to the fact that the polymer additive’s capability as a drag reducer can be permanently crippled when subjected to high shear rates or exposed to prolonged period of turbulent flow and repeated heating and cooling. In contrast to the polymer additives, mechanical degradation of surfactant additives when exposed to regions of high shear stress or repeated heating and cooling is only temporary. In the present study, a two-dimensional water tunnel was designed and fabricated to investigate drag reduction by surfactant additives. Flow development check experiments were performed with different concentrations of surfactant additives to justify the fully developed flow conditions at the test section. The results indicate that the hydrodynamic entry length for water flow without surfactants is very short. For surfactant concentrations of 20, 60, 120 and 160 ppm, the entry lengths were about 300, 500, 1200 and 1400 mm respectively. The entry length for the surfactant concentration of 200 ppm was consistent with that of 160 ppm.